Effectiveness of an Educational Feedback Intervention on Drug Prescribing in Dental Practice - Rauniar, GP; Das, BP; Manandhar, TR; Bhattacharya, SK (Kathmandu University Medical Journal, 2014)
Background Irrational use of drugs as well as inappropriate and over drug prescribing leads to unnecessary expenditures and emergence of resistant bacterial strains. Feedback intervention on drug prescribing habits and face to face educational intervention of prescription audit would be effective in rationalizing prescribing practices. Objective To measure the impact of educational feedback intervention on the prescribing behavior of dental surgeons. Methods Prospective audit of twelve hundred outpatients prescriptions in dental OPD at BPKIHS of those dental surgeon who attended the educational intervention session was collected randomly by trained persons on customized data collection sheet before and after educational intervention. Results A total 1200 prescription were collected, 300 before and 300 after intervention period at the internal of one month, three months and six months. Majority of the prescriptions (39.33%) contained four drugs but after intervention, prescriptions contained mostly one drug, 73% in first month, 78.67% in third month and 65.34% in six month. Mean number of drugs per prescription after intervention were decreased. There was increased number of generic names of drugs after intervention. Amoxicillin, Metronidazole, Chlorhexidine, Povidone iodine gargle, Nimesulide, Ibuprofen, Ibuprofen + paracetamol, and Paracetamol were most commonly prescribed by dental prescribers before and after intervention. Selection of antimicrobial was done on empirical basis which was correct because Amoxicillin concentration reaches effectively in gingival crevicular fluid and Metronidazole covered effectively against anaerobic bacteria were found in orodental infection. The uses of topical anti-infective preparation as irrigants of choice that can kill majority of micro-organisms found is root canal and dental tubules and minimize systemic use of antimicrobials. Nimesulide prescribing needs to be rationalized. Conclusion Feedback educational intervention of prescription audit is effective to improve their prescribing behaviors and rationalize drug utilization pattern for the benefit of the patients. DOI: http://dx.doi.org/10.3126/kumj.v10i4.10991 Kathmandu Univ Med J 2012;10(4):30-35